Comparative Effectiveness of Cerclage With and Without Adjunctive Therapy on Maternal-Fetal Outcomes [25N]. (May 2016) - Adams, Jacquelyn H.; Sangtani, Ajleeta; Liew, Zi-Qi; Kenny, Tiffany; McCarroll, Michele L.; Silber, Angela
Abstract : INTRODUCTION: Often cerclage, alone and in combination with antibiotic coverage, progesterone, and tocolytics are used in women at high risk of preterm birth or cervical insufficiency. METHODS: A retrospective chart review of women who underwent history- or ultrasound-indicated transvaginal cervical cerclage at 12 to 24 gestation. Patients were divided into two groups: cerclage only (CO) or cerclage with adjunctive therapy (CAT). Outcomes of race, insurance type, maternal age (MA), gestational age at placement (GAAP), time from cerclage placement to delivery (TCTD), gestational age at presentation (GAPR), neonatal intensive care unit admission (NICU), APGAR 1-minute (APGAR) were analyzed using SPSS 22.0. RESULTS: No significant differences were noted in general demographics between the CO (n=112) and CAT (n=52) groups in race: White 36% versus 44%, African/American 51% versus 55%, Other 11% versus 6%, ( P =.394); insurance type: public 51% and private 48% versus public 55% and private 44% P =.652; MA: 28±5 years, 29±5 years, ( P =.211); and GAAP: 115±25 days versus 118±5 days, ( P =.804), respectively. Similarly, no significant differences were noted in maternal-fetal outcomes between CO and CAT for TCTD: 130±45 days, 133±46 days, ( P =.723); GAPR: 243±39 days, 245±35 days, ( P =.804); NICU: 36 admissions versus 18 admissions, ( P =.807); and APGAR: 7±2.3, 7.1±2.3, ( P =.834), respectively. CONCLUSION: These results indicate that the use of cerclage or cerclage with adjunctive therapy does not provide additional benefits. Further studies with larger samples are encouraged to continue evaluation of the best treatment approach.